COVID-19 EFFECT ON TOURISM INDUSTRY IN INDIA - Chitra Guha , Madhup K. Gandhi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Corona virus is a pandemic that spreads mainly through contact with any person when they cough and sneeze. Covid-19 pandemic started in China and is then spreading in the world, which is the main cause of large number of deaths (40,598 deaths, 1st April 2020). Covid-19 is a disease in which a person has respiratory disease with symptoms such as severe fever and difficulty in breathing in more severe cases. To prevent the epidemic, many countries also initiated a lockdown process to prevent the number of infections of the disease. This lock down ordered by the government severely affected the lives of the Arabs. And at the same time became a major cause of economic collapse. This is the reason why the country with the highest covid-19 transition recorded a high increase in unemployment. This paper calculates the impact of Covid-19 for affected countries worldwide and their tourism industry. This paper is mainly based on covid-19 in India which analyzes the impact it has had on tourism and hotel industry. Tourism and hotel industry is suffering from covid-19 crisis worldwide. India is the largest country in the world which is rich in various tourism resources, millions of tourists come here annually, which makes a significant contribution to the GDP of the country. Some initial steps need to be taken to overcome the current slowdown in the eco-tourism industry. This paper analyzes their long-term impact.